EFEKTIVITAS EKSTRAK BAWANG PUTIH ( Allium sativum L ) TERHADAP PERBAIKAN KUALITAS IKAN SELUANG ( Rasbora caudimaculata) KERING BENTUK BUTTERFLY - Juhana Suhanda; Agustiana Agustiana (Fish Scientiae, 2019)
This study aims to know and determine the effectivity of optimum addition of garlic (Allium sativum L) on the dry butterfly-shaped greater scissortail fish (Rasbora caudimaculata) quality. The benefit of the study is an information source on the benefit of garlic on the dry scissortail product and as one of the diversification form of fisheries processed products. It was conducted in Fish Processing Laboratory of Faculty of Fisheries and Marine Science, UNLAM, Banjarbaru, and Basic Science Laboratory,UNLAM, Banjarbaru. The study was done for 3 months covering laboratory analysis, data analysis and reporting. It used a Complete Randomized Design with 4 treatments each of which with 3replications. Treatment O was taken as control, 5% salt solution immersion, A: immersionin 5% salt solution added with 10% garlic extract, B: immersion in 5% salt solution added with 15% garlic extract, and C: immersion in 5% salt solution added with 20% garlicextract. Data included chemical test, such as water content, fat, and protein, andorganoleptic test, such as taste, aroma, color, and texture. Results showed that the lowest mean water content was found in treatment B,16.65%, fat in treatment O, 12.5066%, and the highest protein content was recorded in treatment O, 50.81%. Immersion in the garlic extract solution did not give significantly different effect on water content, fat, and protein of the dry butterfly-shaped greaterscissortail. The organoleptic test reflected that the panellists preferred the taste and aromaof the dry butterfly great scissortail at treatment C, treatment O for color, and treatment Afor texture. As conclusion, treatment C gave the best quality of the dry butterfly-shaped great scissortail product.